Regenerated cellulose fiber as well as preparation method and application thereof
Through the three-stage solidification bath technology, the internal hollow large pores and outer nano-scale small pore structures of the regenerated cellulose fibers are constructed, which solves the problems of complex preparation, high cost and poor mechanical properties of cellulose fibers in the prior art, and achieves high efficiency and warmth preservation , comprehensive effects of breathability and hygroscopicity, suitable for high-end clothing applications.
Patent Information
- Application Number
- CN202411414926.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
AI Technical Summary
The existing hollow structure preparation technology for regenerated cellulose fibers is complex, has high cost, poor mechanical properties, and is difficult to simultaneously improve warmth, breathable and hygroscopicity.
Using the three-stage solidification bath technology, by adding pore-forming agent, dispersing agent and crosslinking agent to the cellulose solution, a unique structure of internal hollow large pores and outer nano-scale small pores is formed, combining acidic solutions and multiple solidification liquids. Accurate regulation and build a three-dimensional network structure.
It significantly improves the warm-keeping performance of fibers, maintains good breathability and hygroscopicity, achieves a perfect combination of warmth and lightweight, reduces production costs, and is suitable for large-scale industrial production.
Smart Images

Figure CN119221145A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new biomass materials, and in particular to a regenerated cellulose fiber and a preparation method and application thereof. Background Art
[0002] As a fiber material derived from natural cellulose resources (such as wood, bamboo, cotton linters, etc.), regenerated cellulose fiber has attracted wide attention in the textile industry due to its good renewability, biodegradability, moisture absorption and breathability. However, regenerated cellulose fibers prepared by traditional processes, such as viscose fiber, modal fiber, lyocell fiber, etc., are mostly solid structures, and their thermal insulation performance mainly depends on increasing the thickness of the fiber fabric. This strategy inevitably sacrifices the lightness and breathability of the fiber while pursuing efficient thermal insulation effects, thus limiting its further expansion and application in the field of high-end thermal clothing.
[0003] Some researchers have explored the construction of hollow structures in regenerated cellulose fibers. The introduction of hollow structures can not only reduce the thermal conductivity of fibers and improve thermal insulation performance, but also increase the fluffiness and resilience of fibers, thereby improving wearing comfort and achieving a perfect combination of thermal insulation and lightweight. However, the preparation technology of hollow fibers mostly focuses on the field of synthetic fibers, such as polyester, nylon, etc. The technical development of hollowing transformation of regenerated cellulose fibers is still in its early stages and still faces the following technical bottlenecks and many technical problems: on the one hand, the preparation process is complicated. The current preparation methods often involve complex chemical reactions and fine process control (coaxial spinning, microfluidics, etc.), which leads to high production costs of hollow fibers and difficulty in achieving scale; on the other hand, in the spinning process, the local pore size of the fiber is often too large or even ruptured and collapsed, resulting in poor hollowness and mechanical properties of the regenerated cellulose fiber, that is, the introduction of hollow structure into the fiber by the existing technology is often accompanied by the sacrifice of fiber strength; moreover, the hollow fibers prepared in the existing technology mostly have a "hollow inside and solid outside" structure, which makes it difficult to simultaneously improve the thermal insulation, air permeability and hygroscopicity of the fiber. Summary of the invention
[0004] The main purpose of the present invention is to provide a regenerated cellulose fiber and a preparation method and application thereof. The technical problem to be solved is how to provide a regenerated cellulose fiber and a preparation method and application thereof, so that the regenerated cellulose fiber has a unique structure of internal hollow macropores and outer nanoscale small pores. This unique structural design not only significantly improves the thermal insulation performance of the fiber, but also takes into account good air permeability and moisture absorption, meeting the comprehensive requirements of modern textile materials for warmth, lightness, comfort and environmental protection; and it has excellent mechanical properties, a simple preparation method and low cost, making it more suitable for practical use.
[0005] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to a method for preparing regenerated cellulose fiber proposed in the present invention, it comprises the following steps:
[0006] S1 dissolving a cellulose raw material in a solvent to obtain a cellulose solution;
[0007] S2 adding a pore-forming agent, a dispersant and a cross-linking agent to the cellulose solution, mixing, and vacuum degassing to obtain a spinning solution;
[0008] S3 spinning stock solution is spun to form stock solution thin streams; the stock solution thin streams are passed through the first coagulation bath, the second coagulation bath and the third coagulation bath in sequence to obtain primary cellulose fibers; the coagulation liquid in the first coagulation bath is an acidic solution, which forms a hollow structure inside the fiber; in the second coagulation bath, a nanoscale pore structure is formed on the outer layer of the fiber; in the third coagulation bath, the acid introduced into the fiber by the first coagulation bath and the solvent introduced into the fiber by the second coagulation bath are replaced by solvent exchange, and the fiber is gelled at the same time to form a three-dimensional network structure;
[0009] S4 primary cellulose fibers are drawn, dried, curled and wound to obtain regenerated cellulose fibers.
[0010] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0011] Preferably, in the aforementioned preparation method, the cellulose raw material is selected from at least one of coniferous wood dissolving pulp, broadleaf wood dissolving pulp, refined cotton, wheat straw dissolving pulp, reed dissolving pulp, straw dissolving pulp, bamboo dissolving pulp, microcrystalline cellulose and nanocellulose; and the mass concentration of cellulose in the cellulose solution is 6 to 12%.
[0012] Preferably, in the aforementioned preparation method, the solvent in step S1 is selected from at least one of NaOH / CS2, N-methylmorpholine-N-oxide aqueous solution, LiCl / N,N-dimethylacetamide, alkali / urea or thiourea aqueous solution, quaternary ammonium / phosphonium salt aqueous solution, ionic liquid and low eutectic solvent.
[0013] Preferably, in the aforementioned preparation method, the pore-forming agent is selected from at least one of sodium carbonate, sodium bicarbonate, calcium carbonate, polyvinyl alcohol and azodicarbonamide; the dispersant is selected from at least one of sodium oleate, carboxylates, sulfate esters, sulfonates, quaternary ammonium salts and pyridinium salts; the cross-linking agent is selected from at least one of polyethylene glycol, polyethylene glycol diglycidyl ether, polyvinyl pyrrolidone, polyacrylamide, epichlorohydrin, isocyanate and sodium chromate; based on the mass of the cellulose raw material as 100%, the added amount of the pore-forming agent is 1 to 50%, the added amount of the dispersant is 0.1 to 20%, and the added amount of the cross-linking agent is 0.1 to 15%.
[0014] Preferably, in the aforementioned preparation method, the acidic solution is selected from at least one of hydrochloric acid, sulfuric acid, phosphoric acid, formic acid, acetic acid, propionic acid, lactic acid, pyruvic acid, thioglycolic acid, 3-mercaptopropionic acid, methoxyacetic acid, ethoxyacetic acid, 2-chloropropionic acid and acrylic acid; the mass concentration of the acidic solution is 0.5-18%; the length of the first coagulation bath is 1-2 m, and the residence time of the stock solution stream in the first coagulation bath is 5-10 min.
[0015] Preferably, in the aforementioned preparation method, the coagulation liquid of the second coagulation bath is selected from at least one of water, methanol, ethanol, n-propanol, isopropanol, tert-butanol, acetone, ether, tetrahydrofuran, ethyl acetate, butyl acetate, methyl ethyl ketone, dimethylformamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, cyclohexane, n-hexane, petroleum ether, dioxane, pyridine, acetonitrile, chloroform, ethylene glycol, nitromethane, methyl formate and aniline; the length of the second coagulation bath is 2 to 4 m, and the residence time of the stock solution stream in the second coagulation bath is 20 to 30 min.
[0016] Preferably, in the aforementioned preparation method, the coagulation liquid of the third coagulation bath is selected from one or two of water, methanol, ethanol, n-propanol, isopropanol, tert-butanol, acetone, ethylene glycol, dioxane, dimethylformamide and dimethyl sulfoxide; the volume ratio of the two coagulation liquids when mixed is 1:1 to 20; the length of the third coagulation bath is 2 to 4 m, and the residence time of the stock solution stream in the third coagulation bath is 15 to 20 min.
[0017] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. A regenerated cellulose fiber proposed in the present invention comprises:
[0018] The fiber body has a hollow structure; the wall layer of the fiber body is a three-dimensional network structure.
[0019] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0020] Preferably, the aforementioned regenerated cellulose fiber has a specific surface area of >160 m 2 / g, hollowness ≥ 80%, density ≤ 0.26g / cm 2 , thermal conductivity ≤0.023W / m·K, dry tensile strength ≥2.07cN / dtex, and dry elongation at break is 9.6~25.8%.
[0021] Preferably, the aforementioned regenerated cellulose fiber is prepared by the aforementioned method for preparing regenerated cellulose fiber.
[0022] The purpose of the present invention and the technical problem solved by the present invention are also achieved by the following technical solutions: The present invention proposes an application of the aforementioned regenerated cellulose fiber in the field of thermal insulation technology.
[0023] By means of the above technical solution, the regenerated cellulose fiber and the preparation method and application thereof proposed in the present invention have at least the following advantages:
[0024] The regenerated cellulose fiber and its preparation method proposed in the present invention add pore-forming agent, dispersant and cross-linking agent to cellulose solution, and accurately construct the unique structure of the fiber through the process of three-stage coagulation bath, so as to obtain regenerated cellulose fiber with a hollow structure inside and a three-dimensional network structure on the outer layer. Specifically, in the technical scheme of the present invention, by adding pore-forming agent to cellulose solution and using acidic solution as coagulation liquid in the first coagulation bath, the pore-forming agent reacts with the acidic solution to foam the inside of the fiber, and a hollow macroporous structure is formed inside the fiber; this structural design effectively reduces the heat conduction area of the fiber, and reduces the efficiency of heat convection and heat conduction; at the same time, in the technical scheme of the present invention, the wall layer of the fiber forms a three-dimensional network structure through the process control of the second coagulation bath and the third coagulation bath; specifically: in the second coagulation bath, by controlling the polarity and molecular size of the coagulation liquid, the nano-scale pore structure of the outer layer of the fiber is accurately controlled; generally, solvent molecules with larger polarity, such as methanol, have stronger interaction with the fiber network, and this strong interaction helps the solvent to better penetrate into the fiber, and helps to form a uniform Uniform pore structure, while solvents with smaller molecular size can make the fiber form more micropores; while solvent molecules with smaller polarity, such as n-hexane, etc., have weak interaction with cellulose molecules, making it difficult for n-hexane to quickly penetrate into the cellulose network, forming an uneven pore structure, while solvents with larger molecular size cause the fiber to form a larger pore size; therefore, the coagulation liquid of the appropriate second coagulation bath can be selected according to the expected design of the product to accurately control the pore structure of the fiber wall layer; then, in the third coagulation bath, on the one hand, the acid introduced into the fiber by the first coagulation bath and the solvent introduced into the fiber by the second coagulation bath are replaced by solvent exchange, and at the same time, the regenerated cellulose fiber molecular chain is further formed with intermolecular and intramolecular hydrogen bonds, thereby gelling into a stable three-dimensional network structure, ensuring that the fiber pores do not collapse in subsequent sections. The present invention forms nanoscale micropores in the outer layer of the fiber by adopting a multi-stage coagulation bath regeneration technology, further enhancing the thermal insulation effect of the fiber, reducing the radiation loss of heat by scattering and reflecting infrared radiation, forming a dual thermal insulation mechanism, and having a good thermal insulation effect.
[0025] The regenerated cellulose fiber and preparation method thereof proposed in the present invention have both an internal hollow structure and an external nano-network structure, so that the fiber can keep warm while still maintaining good air permeability and hygroscopicity, avoiding the stuffiness caused by traditional thermal insulation materials, improving the comfort of wearing, and making the fiber material more adaptable to the human body's needs for thermal and hygroscopic comfort. Compared with traditional solid fiber materials, it has a lower weight under the same thermal insulation effect, achieving a perfect combination of warmth and lightness. This is particularly important in the fields of outdoor sports equipment, winter clothing, etc.
[0026] The regenerated cellulose fiber and its preparation method and application proposed in the present invention prepare a spinning solution by adding a dispersant to a cellulose solution, thereby ensuring the uniform distribution of each component in the cellulose solution in the dispersion, effectively preventing the collapse of the internal structure of the fiber during the molding process, thereby significantly improving the hollowness of the fiber; at the same time, adding a cross-linking agent to the cellulose solution to prepare the spinning solution further strengthens the intermolecular bonding force inside the fiber, improves the overall strength and durability of the fiber, and enables the fiber to maintain excellent mechanical properties in a variety of application environments.
[0027] The regenerated cellulose fiber and the preparation method thereof proposed in the present invention utilize cellulose as raw material and prepare the regenerated cellulose fiber through a dissolution and spinning regeneration process. The raw material source is extensive and renewable, reducing the dependence on natural resources. At the same time, the solvents used in the preparation process can be recycled or harmlessly treated through proper treatment, reducing pollution to the environment, and complying with the concepts of green production and sustainable development.
[0028] The preparation method of the regenerated cellulose fiber proposed in the present invention has a simple process flow, mild reaction conditions, and can be prepared continuously. By adjusting parameters such as the type and concentration of the pore-forming agent in the spinning solution and the conditions of the coagulation bath, the formation of the hollow structure and nanoscale micropores can be accurately controlled, thereby achieving customized design of the thermal insulation performance of the fiber. The method is suitable for large-scale industrial production, which is beneficial to reducing production costs and improving product market competitiveness.
[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a scanning electron microscope image of a cross section of regenerated cellulose fiber prepared in Example 1 of the present invention;
[0031] Figure 2 is a photograph of the regenerated cellulose fiber prepared in Example 1 of the present invention;
[0032] Figure 3 is a scanning electron microscope image of a cross section of an outer layer of regenerated cellulose fiber prepared in Example 1 of the present invention;
[0033] Figure 4 is a scanning electron microscope image of the surface of the regenerated cellulose fiber prepared in Example 1 of the present invention;
[0034] Figure 5 This is a polarizing microscope image of the regenerated cellulose fiber prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a regenerated cellulose fiber and its preparation method and application according to the present invention, its specific implementation, structure, characteristics and effects, in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0036] The present invention provides a method for preparing regenerated cellulose fiber, which comprises the following steps:
[0037] The first step is to prepare a cellulose solution; specifically, the cellulose raw material is dissolved in a corresponding solvent; the cellulose raw material can be cellulose raw material purchased from the market; and the solvent can be a solvent corresponding to the cellulose raw material.
[0038] In order to ensure the physical properties of the fiber, in a specific embodiment of the present invention, the cellulose raw material is selected from at least one of coniferous wood dissolving pulp, broadleaf wood dissolving pulp, refined cotton, wheat straw dissolving pulp, reed dissolving pulp, straw dissolving pulp, bamboo dissolving pulp, microcrystalline cellulose and nanocellulose. Further, the cellulose raw material is preferably at least one of coniferous wood dissolving pulp, broadleaf wood dissolving pulp and refined cotton.
[0039] In order to dissolve cellulose better and facilitate the subsequent spinning process, the solvent for dissolving cellulose is selected from at least one of NaOH / CS2, N-methylmorpholine-N-oxide aqueous solution, LiCl / N, N-dimethylacetamide, alkali / urea or thiourea aqueous solution, quaternary ammonium / phosphonium salt aqueous solution, ionic liquid and low eutectic solvent. Further, in order to ensure the dissolution efficiency and dissolution quality of cellulose, the solvent for dissolving cellulose is preferably NaOH / CS2, N-methylmorpholine-N-oxide (NMMO) aqueous solution, alkali / urea or thiourea aqueous solution, imidazole acetate ionic liquid, super alkali acetate ionic liquid, imidazole chloride ionic liquid and imidazole hydrogen sulfate ionic liquid. In the above expression, NaOH / CS2 refers to a mixed aqueous solution of NaOH and CS2, LiCl / N, N-dimethylacetamide refers to a mixed aqueous solution of LiCl and N, N-dimethylacetamide, alkali / urea or thiourea aqueous solution refers to a mixed aqueous solution of alkali and urea or thiourea, and quaternary ammonium / phosphonium salt aqueous solution refers to a mixed aqueous solution of quaternary ammonium salt and phosphate.
[0040] When the cellulose raw material is dissolved, the mass concentration of the cellulose solution is generally controlled so that it can be well spun in the subsequent process. When the mass concentration of the cellulose solution is too high, the viscosity of the cellulose solution is too large, which is not conducive to the extrusion of the spinning solution from the spinneret; when the mass concentration of the cellulose solution is too low, the fiber forming effect is poor; in order to smoothly spin in the subsequent process and obtain fibers of good quality, the present invention preferably controls the mass concentration of cellulose in the cellulose solution to be 6-12%; further, the mass concentration of cellulose in the cellulose solution is preferably 10-12%.
[0041] The second step is to prepare the spinning solution; the composition of the spinning solution is one of the key points of the technical solution of the present invention. The specific steps are to add pore-forming agent, dispersant and cross-linking agent to the cellulose solution, mix them evenly, and vacuum degas to obtain the spinning solution.
[0042] The technical purpose of adding the pore former to the cellulose solution is to enable it to interact with the coagulation liquid in the subsequent coagulation bath to form a hollow macroporous structure in the fiber.
[0043] In a specific embodiment of the present invention, the pore-forming agent is selected from at least one of sodium carbonate, sodium bicarbonate, calcium carbonate, polyvinyl alcohol and azodicarbonamide. The pore-forming agents used in the present invention can be purchased from the market.
[0044] The amount of pore-forming agent added is related to the morphology and quantity of the hollow macroporous structure inside the fiber. When the amount added is too low, it may cause uneven distribution of the hollow macroporous structure, so that the hollow structure will not be formed locally in the fiber, affecting the thermal insulation performance of the fiber; when the amount added is too high, it may cause the volume of the hollow macropores to be too large, resulting in the fiber wall being too thin or even the hollow structure being broken, resulting in a decrease in mechanical properties. In order to better balance the thermal insulation and mechanical properties of the fiber and obtain fibers with excellent comprehensive properties, the present invention preferably controls the amount of pore-forming agent added to 1 to 50% of the mass of cellulose; further, it is preferred to control the amount of pore-forming agent added to 5 to 30% of the mass of cellulose; further, it is preferred to control the amount of pore-forming agent added to 5 to 15% of the mass of cellulose.
[0045] The technical purpose of adding a dispersant to the cellulose solution is to ensure that the components in the cellulose solution are evenly distributed in the dispersion, effectively preventing the hollow macroporous structure inside the fiber from collapsing during the fiber forming process, thereby increasing the hollowness of the fiber.
[0046] In a specific embodiment of the present invention, the dispersant is selected from at least one of sodium oleate, carboxylates, sulfate esters, sulfonates, quaternary ammonium salts and pyridinium salts. The dispersants used in the present invention can be purchased from the market.
[0047] The amount of dispersant added is closely related to the quality of the spinning solution and the subsequent spinnability. When the amount added is too low, it may lead to poor dispersion of other additives in the solution, prone to agglomeration, and affect the uniformity of the spinning solution; when the amount added is too high, it may increase the solid content of the solution and increase the viscosity, which is not conducive to the extrusion of the spinning solution from the spinneret. In order to better balance the uniformity of the spinning solution and the smoothness of spinning, the present invention preferably controls the amount of dispersant added to 0.1-20% of the mass of cellulose; further, it is preferred to control the amount of dispersant added to 0.5-15% of the mass of cellulose; further, it is preferred to control the amount of dispersant added to 5-15% of the mass of cellulose; further, it is preferred to control the amount of dispersant added to 10-15% of the mass of cellulose.
[0048] The technical purpose of adding a cross-linking agent to the cellulose solution is to further strengthen the intermolecular bonding force within the fiber, improve the overall strength and durability of the fiber, and enable the fiber to maintain excellent mechanical properties in a variety of application environments.
[0049] In a specific embodiment of the present invention, the cross-linking agent is selected from at least one of polyethylene glycol, polyethylene glycol diglycidyl ether, polyvinyl pyrrolidone, polyacrylamide, epichlorohydrin, isocyanate and sodium chromate. The cross-linking agents used in the present invention can be purchased from the market.
[0050] The amount of crosslinking agent added has a great influence on the performance of the fiber. When the amount added is too low, the crosslinking reaction may be insufficient, so that the performance of the fiber cannot meet the expected requirements; when the amount added is too high, the plasticity and ductility of the fiber in subsequent processing (such as stretching, curling, etc.) may deteriorate, affecting the processing efficiency and product quality. In order to better balance the comprehensive performance of the fiber, the present invention preferably controls the amount of crosslinking agent added to 0.1-15% of the mass of cellulose; further, it is preferred to control the amount of crosslinking agent added to 2-15% of the mass of cellulose; further, it is preferred to control the amount of crosslinking agent added to 5-15% of the mass of cellulose.
[0051] After the pore-forming agent, dispersant and cross-linking agent are uniformly mixed in the cellulose solution, it is necessary to perform vacuum degassing treatment to ensure the quality of the spinning solution and avoid the phenomenon of broken fibers that may occur during the spinning process due to the presence of bubbles in the spinning solution.
[0052] During vacuum degassing, appropriate degassing temperature and degassing time can maximize the quality of the spinning solution and the performance of subsequent products. The degassing temperature is generally controlled to be 25-90°C, more preferably 30-80°C; the degassing time is 0.5-15h, preferably 1-10h. In a specific embodiment of the present invention, the vacuum degassing temperature is 30-90°C, and the vacuum degassing time is 2-10h. The reason for setting the degassing parameters in this way is that when the degassing temperature is too low or the degassing time is too short, the spinning solution is not completely degassed, which makes it easy to break the wire during the spinning process; when the degassing temperature is too high or the degassing time is too long, it may cause the spinning solution to deteriorate or the fiber to degrade, resulting in a decrease in the quality of the regenerated cellulose fiber.
[0053] The third step is spinning; first, the spinning solution is sprayed to form a thin stream of solution; then the thin stream of solution flows through a coagulation bath to coagulate; finally, the fiber is stretched, dried, curled, and wound.
[0054] In the above spinning step, the spinning solution can be spun by conventional spinning processes in the art, as long as the spinning solution can be formed into a thin stream of the solution. In a specific embodiment of the present invention, the spinning solution is extruded from the spinneret at a pressure of 0.5 MPa and a temperature of 25 to 110° C. at a speed of 0.5 to 5 m / min to the first coagulation bath, the second coagulation bath and the third coagulation bath for spinning to obtain primary cellulose fibers. The above spinning process parameters are set so that the spinning solution can be quickly extruded from the spinneret to form a thin stream of the solution. Preferably, the pore size of the spinneret is 0.1 to 0.3 mm, the number of spinneret holes on the spinneret is 100 to 200, and the preferred spinning method is wet spinning or dry-jet wet spinning.
[0055] In the above spinning steps, the most core and critical step is the setting of the coagulation bath; in the technical solution of the present invention, a three-stage coagulation bath is set, that is, the stock solution stream passes through the first coagulation bath, the second coagulation bath and the third coagulation bath in sequence to obtain primary cellulose fibers. In the three-stage coagulation bath, the coagulation liquid of the first coagulation bath is an acidic solution, which is mainly used to form a hollow structure inside the fiber. Specifically, the pore-forming agent in the spinning stock solution reacts with the acidic solution to foam the inside of the fiber, forming a hollow macroporous structure inside the fiber; then, through the process control of the second coagulation bath and the third coagulation bath, the wall layer of the fiber forms a three-dimensional network structure; specifically: in the second coagulation bath, by controlling the polarity and molecular size of the coagulation liquid, the nanoscale pore structure of the outer layer of the fiber is precisely controlled; generally, solvent molecules with larger polarity, such as methanol, have a stronger interaction with the fiber network. This strong interaction helps the solvent to better penetrate into the fiber and helps to form a uniform pore structure. At the same time, solvents with smaller molecular size The fiber can be made to form more micropores; while the solvent molecules with smaller polarity, such as n-hexane, have weak interactions with cellulose molecules, making it difficult for n-hexane to quickly penetrate into the cellulose network, forming an uneven pore structure, while the solvent with larger molecular size causes the fiber to form a larger pore size; therefore, the coagulation liquid of the appropriate second coagulation bath can be selected according to the expected product design to accurately control the pore structure of the fiber wall layer; in the third coagulation bath, on the one hand, the acid introduced into the fiber by the first coagulation bath and the solvent introduced into the fiber by the second coagulation bath are replaced by solvent exchange, and at the same time, the regenerated cellulose fiber molecular chain further forms intermolecular and intramolecular hydrogen bonds, thereby gelling into a stable three-dimensional network structure, ensuring that the fiber pores do not collapse in subsequent sections. The present invention forms nanoscale micropores in the outer layer of the fiber by adopting the three-stage coagulation bath regeneration technology, so that the fiber has a unique structure of internal hollow and external sparse, so that it has good thermal insulation effect and mechanical properties, and excellent comprehensive performance.
[0056] In order to better control the structure of the fiber, in the three-stage coagulation bath, the coagulation liquid of the first coagulation bath is an acidic solution; the acidic solution is selected from at least one of hydrochloric acid, sulfuric acid, phosphoric acid, formic acid, acetic acid, propionic acid, lactic acid, pyruvic acid, mercaptoacetic acid, 3-mercaptopropionic acid, methoxyacetic acid, ethoxyacetic acid, 2-chloropropionic acid and acrylic acid. The acids used in the present invention can all be purchased from the market. The length of the first coagulation bath is set to 1 to 2 meters, and the residence time of the stock solution stream in the first coagulation bath is 5 to 10 minutes.
[0057] In the first coagulation bath, the concentration of the acid solution is the key to the foaming of the pore-forming agent and the formation of hollow fibers. If the acid concentration is too high, it may accelerate the reaction rate of the pore-forming agent and the acid solution, making the foaming process difficult to control, producing excessive bubbles and deforming the fibers; at the same time, high concentrations of acid will also cause degradation of the fiber material, affecting the mechanical properties and structural stability of the fibers; and when the acid concentration is too low, the pore-forming agent and the acid solution may not react fully, resulting in poor foaming effects and reduced hollowness of the regenerated cellulose fibers. In order to balance the comprehensive properties of the fibers, the mass concentration of the acid used in the first coagulation bath of the present invention is 0.5-18%; further, the mass concentration of the acid is preferably 1-12%.
[0058] The second coagulation bath is mainly used to form a structure with nanoscale pores in the wall layer of the hollow fiber; the coagulation liquid of the appropriate second coagulation bath can be selected according to the expected product design to accurately control the pore structure of the fiber wall layer.
[0059] The coagulation liquid of the second coagulation bath is selected from at least one of water, methanol, ethanol, n-propanol, isopropanol, tert-butanol, acetone, ether, tetrahydrofuran, ethyl acetate, butyl acetate, methyl ethyl ketone, dimethylformamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, cyclohexane, n-hexane, petroleum ether, dioxane, pyridine, acetonitrile, chloroform, ethylene glycol, nitromethane, methyl formate and aniline; the organic reagents used in the present invention can be purchased from the market. The length of the second coagulation bath set by the present invention is 2 to 4 meters, and the residence time of the stock solution stream in the second coagulation bath is 20 to 30 minutes.
[0060] The role of the third coagulation bath mainly includes two aspects. The first is to replace the acid and organic solvent introduced by the first two coagulation baths by solvent exchange; the second is to make the molecular chains of the regenerated cellulose fibers further form intermolecular and intramolecular hydrogen bonds, thereby gelling the nanoscale pore structure formed in the second coagulation bath into a stable three-dimensional network structure, ensuring that the fiber pores do not collapse in subsequent processes.
[0061] The third coagulation bath is selected from water, methanol, ethanol, n-propanol, isopropanol, tert-butanol, acetone, dimethylformamide, dimethyl sulfoxide, etc., but not limited to a mixed solution of one or two thereof, and the volume ratio of the two coagulation solutions when mixed is 1:1 to 20. The organic reagents used in the present invention can all be purchased from the market. The length of the third coagulation bath set by the present invention is 2 to 4 m, and the residence time of the stock solution stream in the third coagulation bath is 15 to 20 min.
[0062] In the above spinning step, the final step is the drawing, drying, curling and winding of the primary cellulose fibers. The process control of this step of the present invention can be controlled by conventional processes in the prior art, and the present invention does not specifically limit this. In a specific embodiment of the present invention, in the drawing step, the drawing multiple of the traction wheel is preferably 1 to 1.2; in the drying step, the preferred drying method is atmospheric pressure drying, freeze drying or supercritical drying; in the curling and winding step, the linear speed of the winding reel is preferably the same as the previous drawing speed.
[0063] The present invention also provides a regenerated cellulose fiber, as shown in the following Figures 1 to 5 , which includes a fiber body; the fiber body has a hollow structure; the wall layer of the fiber body is a three-dimensional network structure.
[0064] The space inside the hollow fiber in the above technical solution can store a large amount of still air, which can significantly reduce the convection and conduction of heat; the nano-scale micropores on the surface, that is, the outer layer, can block the path of heat conduction, making the transfer of heat inside the fiber more difficult. In addition, the micropores may also have a certain scattering and reflection effect on thermal radiation, reducing the radiation loss of heat, thereby further improving the thermal insulation effect of the fiber.
[0065] In a specific embodiment of the present invention, the specific surface area of the regenerated cellulose fiber is greater than 160 m 2 / g, hollowness ≥ 80%, density ≤ 0.26g / cm 2 , thermal conductivity ≤0.023W / (m·K), dry tensile strength ≥2.07cN / dtex, and dry elongation at break (9.6~25.8%).
[0066] In a specific embodiment of the present invention, the regenerated cellulose fiber is prepared by the aforementioned method for preparing regenerated cellulose fiber.
[0067] The present invention also proposes an application of the aforementioned regenerated cellulose fiber in the field of thermal insulation technology.
[0068] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0069] Unless otherwise specified, the materials, reagents, etc. mentioned below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0070] Example 1
[0071] Refined cotton was dissolved in an aqueous solution of N-methylmorpholine-N-oxide (NMMO) to obtain a cellulose solution with a mass concentration of 10%. To the cellulose solution, 10% of the mass of cellulose as a pore-forming agent, 15% of a dispersant, sodium sulfonate, and 15% of a cross-linking agent, polyethylene glycol, were added, mixed evenly, and vacuum degassed at 80°C for 4 hours to obtain a uniform spinning solution.
[0072] The spinning solution was extruded from the spinneret at a speed of 0.5 m / min at a pressure of 0.5 MPa and a temperature of 90°C. The regenerated cellulose fiber was prepared by wet spinning process, and the aperture of the 100-hole spinneret was 0.3 mm. The three-stage coagulation baths were 2% sulfuric acid solution, methanol, and tert-butyl alcohol, respectively. After 1.1 times of drafting, the fiber stayed in the three-stage coagulation baths for 10 min, 20 min, and 20 min, respectively. After freeze drying, the fiber was curled to obtain regenerated cellulose fiber, such as Figure 2 shown.
[0073] The scanning electron microscope and polarizing microscope photos of the regenerated cellulose prepared in this example are as follows: Figure 1 , 3 As shown in Figure 5, it can be seen that the regenerated cellulose fiber has an internal hollow structure ( Figure 1 , Figure 5 ), while the outer layer and surface are three-dimensional network structures ( Figure 3 , Figure 4 ).
[0074] The specific properties of the regenerated cellulose fiber prepared in this example are shown in Table 1. The test methods for various properties are all tested using conventional test methods in the art.
[0075] Example 2
[0076] Refined cotton was dissolved in an aqueous solution of N-methylmorpholine-N-oxide (NMMO) to obtain a cellulose solution with a mass concentration of 10%. To the cellulose solution, 5% of the mass of cellulose as a pore-forming agent, 10% of sodium oleate as a dispersant, and 5% of polyethylene glycol diglycidyl ether as a cross-linking agent were added, and after uniform mixing, vacuum degassing was performed at 80°C for 4 hours to obtain a uniform spinning solution.
[0077] The spinning solution is extruded from the spinneret at a speed of 0.5 m / min at a pressure of 0.5 MPa and a temperature of 90°C. The regenerated cellulose fiber is prepared by a wet spinning process, and the aperture of the 100-hole spinneret is 0.3 mm. The three coagulation baths are 5% acetic acid solution, ethanol, and ethanol, respectively. After 1.1 times of drafting, the fiber stays in the three coagulation baths for 10 min, 20 min, and 20 min, respectively. After freeze drying, the regenerated cellulose fiber is curled.
[0078] The specific properties of the regenerated cellulose fiber prepared in this example are shown in Table 1.
[0079] Example 3
[0080] Dissolve coniferous wood dissolving pulp in an alkali / urea solution to obtain a cellulose solution with a mass concentration of 12%. Add 15% of the mass of cellulose as a pore-forming agent calcium carbonate, 10% of a dispersant sodium oleate and 10% of a cross-linking agent epichlorohydrin to the cellulose solution, mix evenly, and vacuum degas at 30°C for 6 hours to obtain a uniform spinning solution.
[0081] The spinning solution was extruded from the spinneret at a speed of 1 m / min at a pressure of 0.5 MPa and a temperature of 25°C. The regenerated cellulose fiber was prepared by wet spinning process, and the aperture of the 150-hole spinneret was 0.2 mm. The three coagulation baths were 12% hydrochloric acid solution, ethyl acetate, and ethanol, respectively. After 1.1 times of drafting, the fiber stayed in the three coagulation baths for 5 min, 20 min, and 15 min, respectively. After freeze drying, the regenerated cellulose fiber was curled.
[0082] The specific properties of the regenerated cellulose fiber prepared in this example are shown in Table 1.
[0083] Example 4
[0084] Dissolve hardwood dissolving pulp in imidazole acetate ionic liquid to obtain a cellulose solution with a mass concentration of 12%. Add 10% of the mass of cellulose as a pore-forming agent polyvinyl alcohol, 5% of a dispersant sodium sulfate and 5% of a cross-linking agent epichlorohydrin to the cellulose solution, mix evenly, and vacuum degas at 80°C for 6 hours to obtain a uniform spinning solution.
[0085] The spinning solution is extruded from the spinneret at a speed of 0.5 m / min at a pressure of 0.5 MPa and a temperature of 25°C. The regenerated cellulose fiber is prepared by dry-jet wet spinning process, and the aperture of the 100-hole spinneret is 0.2 mm. The three-stage coagulation bath is 0.5% acetic acid solution, water, and tert-butyl alcohol, respectively. After 1.1 times of drafting, the fiber stays in the three-stage coagulation bath for 5 minutes, 30 minutes, and 15 minutes, respectively. After freeze drying, the regenerated cellulose fiber is curled.
[0086] The specific properties of the regenerated cellulose fiber prepared in this example are shown in Table 1.
[0087] Example 5
[0088] Refined cotton was dissolved in imidazole acetate ionic liquid to obtain a cellulose solution with a mass concentration of 10%. Sodium bicarbonate, a pore-forming agent equivalent to 10% of the mass of cellulose, 1% of sodium sulfonate, a dispersant, and 2% of polyethylene glycol, a cross-linking agent, were added to the cellulose solution, mixed evenly, and vacuum degassed at 80°C for 6 hours to obtain a uniform spinning solution.
[0089] The spinning solution is extruded from the spinneret at a speed of 0.5 m / min at a pressure of 0.5 MPa and a temperature of 25°C. The regenerated cellulose fiber is prepared by dry-jet wet spinning process, and the aperture of the 100-hole spinneret is 0.2 mm. The three-stage coagulation bath is 1% sulfuric acid solution, methanol, and water, respectively. After 1.1 times of drafting, the fiber stays in the three-stage coagulation bath for 10 minutes, 30 minutes, and 15 minutes, respectively. After drying at normal pressure, the regenerated cellulose fiber is curled to obtain the regenerated cellulose fiber.
[0090] The specific properties of the regenerated cellulose fiber prepared in this example are shown in Table 1.
[0091] Example 6
[0092] The softwood dissolving pulp was dissolved in imidazole hydrogen sulfate ionic liquid to obtain a cellulose solution with a mass concentration of 10%. 10% of the mass of cellulose as a pore-forming agent calcium carbonate, 3% of a dispersant sodium sulfonate and 5% of a cross-linking agent polyacrylamide were added to the cellulose solution, and after uniform mixing, vacuum degassing was performed at 80°C for 8 hours to obtain a uniform spinning solution.
[0093] The spinning solution was extruded from the spinneret at a speed of 0.5 m / min at a pressure of 0.5 MPa and a temperature of 25°C. The regenerated cellulose fiber was prepared by dry-jet wet spinning process, and the aperture of the 100-hole spinneret was 0.2 mm. The three-stage coagulation baths were 1% sulfuric acid solution, isopropanol, and water, respectively. After 1.1 times of drafting, the fiber stayed in the three-stage coagulation baths for 5 min, 20 min, and 20 min, respectively. After drying at normal pressure, the regenerated cellulose fiber was curled to obtain the regenerated cellulose fiber.
[0094] The specific properties of the regenerated cellulose fiber prepared in this example are shown in Table 1.
[0095] Comparative Example 1
[0096] The same as Example 1, except that no dispersant and cross-linking agent were added. The specific properties of the regenerated cellulose fiber prepared in this comparative example are shown in Table 1.
[0097] Comparative Example 2
[0098] The same as Example 3, except that no pore-forming agent was added. The specific properties of the regenerated cellulose fiber prepared in this comparative example are shown in Table 1.
[0099] Comparative Example 3
[0100] The same as Example 5, except that the second coagulation bath and the third coagulation bath are not provided. The specific properties of the regenerated cellulose fiber prepared in this comparative example are shown in Table 1.
[0101] Table 1
[0102]
[0103]
[0104] It can be seen from the test data of the above examples that the regenerated cellulose fiber prepared by the technical solution of the present invention has excellent comprehensive performance, and has a high specific surface area (>160m 2 / g), high porosity (≥80%), low density (≤0.26g / cm 2 ), low thermal conductivity (≤0.023W / (m·K)), and good mechanical properties (dry tensile strength ≥2.07cN / dtex, dry elongation at break 9.6~25.8%), as shown in Examples 1 to 6.
[0105] It can be seen from the test data of the above comparative examples that, for example, comparative example 1, the only difference from example 1 is that no dispersant and cross-linking agent are added to the spinning solution; it can be seen from the test results that the specific surface area of the regenerated cellulose fiber obtained in comparative example 1 is 66% lower than that in example 1, the hollowness is 39% lower than that in example 1, the thermal conductivity is 100% higher than that in example 1, the density is 224% higher than that in example 1, the dry tensile strength is 91% lower than that in example 1, and the dry elongation at break is 80% lower than that in example 1, that is, the thermal insulation performance and mechanical properties of comparative example 1 are greatly deteriorated; this may be because no dispersant and cross-linking agent are added to the spinning solution in comparative document 1, the components in the regenerated cellulose fiber are uneven, there are many defects in the fiber during the molding process, and the binding force between cellulose molecules is weak, which makes the fiber easy to collapse during the subsequent drying process, resulting in its poor performance.
[0106] It can be seen from the test data of the above comparative examples that, for example, comparative example 2, the only difference from example 3 is that no pore-forming agent is added to the spinning solution; it can be seen from the test results that the specific surface area of the regenerated cellulose fiber obtained in comparative example 2 is 62% lower than that in example 3, the hollowness completely disappears, the thermal conductivity is 306% higher than that in example 3, the density is 594% higher than that in example 3, the dry tensile strength is 21% lower than that in example 3, and the dry elongation at break is 48% lower than that in example 3, that is, the thermal insulation performance and mechanical properties of comparative example 2 are greatly deteriorated; this may be because no pore-forming agent is added to the spinning solution in comparative document 2, and the regenerated cellulose fiber fails to foam in the first coagulation bath, resulting in the formation of solid regenerated cellulose fibers, the fibers have a larger density and a lower specific surface area, and since there is no hollow structure to store air and hinder heat conduction, its thermal insulation effect is poor.
[0107] It can be seen from the test data of the above comparative examples that, as in comparative example 3, the only difference between it and embodiment 5 is that the stock solution stream is not coagulated by a multi-stage coagulation bath; it can be seen from the test results that the specific surface area of the regenerated cellulose fiber obtained in comparative example 3 is reduced by 99% compared with embodiment 5, the hollowness is reduced by 6%, the thermal conductivity is increased by 81% compared with embodiment 5, and the density is increased by 125% compared with embodiment 5, that is, there is no multi-stage coagulation bath regulation in comparative example 3, and the regenerated cellulose fiber prepared therefrom forms a regenerated cellulose fiber with a "hollow inside and solid outside" structure; although a hollow structure is formed inside the fiber, the outer layer of the fiber does not form nano-scale pores, nor does it form a three-dimensional network structure. Since the outer wall of the fiber does not have a loose and porous network structure, its hindering effect on heat conduction and the scattering effect of thermal radiation are both weak, which is manifested as its thermal conductivity is higher than that of embodiment 5, and the thermal insulation effect is poor; at the same time, since the outer wall of the fiber does not have a loose and porous network structure, its density is greater than that of embodiment 5, on the one hand, the clothes are difficult to be lightweight, and on the other hand, the air permeability and hygroscopicity of the fiber are poor, which reduces the comfort of wearing.
[0108] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0109] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing regenerated cellulose fiber, characterized in that: It includes the following steps: S1 dissolving a cellulose raw material in a solvent to obtain a cellulose solution; S2 adding a pore-forming agent, a dispersant and a cross-linking agent to the cellulose solution, mixing, and vacuum degassing to obtain a spinning solution; S3 spinning stock solution is spun to form stock solution thin streams; the stock solution thin streams are passed through the first coagulation bath, the second coagulation bath and the third coagulation bath in sequence to obtain primary cellulose fibers; the coagulation liquid in the first coagulation bath is an acidic solution, which forms a hollow structure inside the fiber; in the second coagulation bath, a nanoscale pore structure is formed on the outer layer of the fiber; in the third coagulation bath, the acid introduced into the fiber by the first coagulation bath and the solvent introduced into the fiber by the second coagulation bath are replaced by solvent exchange, and the fiber is gelled at the same time to form a three-dimensional network structure; S4 primary cellulose fibers are drawn, dried, curled and wound to obtain regenerated cellulose fibers.
2. The preparation method according to claim 1, characterized in that: The cellulose raw material is selected from at least one of softwood dissolving pulp, hardwood dissolving pulp, refined cotton, wheat straw dissolving pulp, reed dissolving pulp, straw dissolving pulp, bamboo dissolving pulp, microcrystalline cellulose and nanocellulose; The mass concentration of cellulose in the cellulose solution is 6-12%.
3. The preparation method according to claim 1, characterized in that: The solvent in step S1 is selected from at least one of NaOH / CS2, N-methylmorpholine-N-oxide aqueous solution, LiCl / N,N-dimethylacetamide, alkali / urea or thiourea aqueous solution, quaternary ammonium / phosphonium salt aqueous solution, ionic liquid and low eutectic solvent.
4. The preparation method according to claim 1, characterized in that: The pore-forming agent is selected from at least one of sodium carbonate, sodium bicarbonate, calcium carbonate, polyvinyl alcohol and azodicarbonamide; the dispersant is selected from at least one of sodium oleate, carboxylates, sulfate esters, sulfonates, quaternary ammonium salts and pyridinium salts; the cross-linking agent is selected from at least one of polyethylene glycol, polyethylene glycol diglycidyl ether, polyvinyl pyrrolidone, polyacrylamide, epichlorohydrin, isocyanate and sodium chromate; based on the mass of the cellulose raw material as 100%, the added amount of the pore-forming agent is 1-50%, the added amount of the dispersant is 0.1-20%, and the added amount of the cross-linking agent is 0.1-15%.
5. The preparation method according to claim 1, characterized in that: The acidic solution is selected from at least one of hydrochloric acid, sulfuric acid, phosphoric acid, formic acid, acetic acid, propionic acid, lactic acid, pyruvic acid, mercaptoacetic acid, 3-mercaptopropionic acid, methoxyacetic acid, ethoxyacetic acid, 2-chloropropionic acid and acrylic acid; the mass concentration of the acidic solution is 0.5-18%; the length of the first coagulation bath is 1-2m, and the residence time of the stock solution stream in the first coagulation bath is 5-10min.
6. The preparation method according to claim 1, characterized in that: The coagulation liquid of the second coagulation bath is selected from at least one of water, methanol, ethanol, n-propanol, isopropanol, tert-butanol, acetone, ether, tetrahydrofuran, ethyl acetate, butyl acetate, methyl ethyl ketone, dimethylformamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, cyclohexane, n-hexane, petroleum ether, dioxane, pyridine, acetonitrile, chloroform, ethylene glycol, nitromethane, methyl formate and aniline; the length of the second coagulation bath is 2 to 4 m, and the residence time of the stock solution stream in the second coagulation bath is 20 to 30 min.
7. The preparation method according to claim 1, characterized in that: The coagulation liquid of the third coagulation bath is selected from one or two of water, methanol, ethanol, n-propanol, isopropanol, tert-butanol, acetone, ethylene glycol, dioxane, dimethylformamide and dimethyl sulfoxide; the volume ratio of the two coagulation liquids when mixed is 1:1-20; the length of the third coagulation bath is 2-4m, and the residence time of the stock solution stream in the third coagulation bath is 15-20min.
8. A regenerated cellulose fiber, characterized in that It includes: A fiber body having a hollow structure; The wall layer of the fiber body is a three-dimensional network structure.
9. The regenerated cellulose fiber according to claim 8, characterized in that Its specific surface area>160m 2 / g, hollowness ≥ 80%, density ≤ 0.26g / cm 2 , thermal conductivity ≤0.023W / m·K, dry tensile strength ≥2.07cN / dtex, and dry elongation at break is 9.6~25.8%.
10. The regenerated cellulose fiber according to claim 8 or 9, characterized in that The regenerated cellulose fiber is prepared by the method for preparing the regenerated cellulose fiber according to any one of claims 1 to 7.
11. Use of the regenerated cellulose fiber according to any one of claims 8 to 10 in the field of thermal insulation technology.
Citation Information
Cited By
Nanometer silicon-based heat-insulation fireproof glass film and preparation method thereof
CN119974707A
Differential cellulose fiber and preparation method thereof
CN120006400A
Odor natural fiber and preparation method thereof
CN120082987A
Crystallization method of carnosine
CN120607489A
MOF in-situ growth regenerated cellulose aerogel fiber as well as preparation method and application thereof
CN121556166A